An improved synthesis of azedarachol - Ran, Gao; Weisheng, Tian (Steroids, 2022)
An improved synthesis of azedarachol is reported in 10 steps with an overall yield of 12% from pregnanetriol. A proper use of p-anisaldehyde dimethyl acetal provided a chance of regioselective reduction of 2-enepregnane-16R,20R-p-anisaldehyde acetal(6) and in turn allowed a selective protection at C16-hydroxy and enabled a stereoselective reduction of C20-ketone to establish the configuration at C20.